Effect of Blending Sodium Lignosulfonate (SLS) and Rice Husk Ash (RHA) for Stabilization of Clay Soil - Tamara, Erlian; Wulandari, Sri (Jurnal Teknik Sipil, 2025)
Clay soils have relatively low bearing capacity and high compressibility. Therefore, it is necessary to improve the soil before construction begins. This research aims to analyze the effect of adding sodium lignosulfonate (SLS) and rice husk ash (RHA) as clay stabilization materials based on the parameter values of soil shear strength, compression coefficient and consolidation coefficient. The clay soil samples in this study came from the Keandra Lagoon housing project area located in Tengah Tani Subdistrict, Cirebon Regency. The results showed that the original soil with the addition of 10% rice husk ash (RHA) and 10% sodium lignosulfonate (SLS) had a deep shear angle of 26.009° with a cohesion of 0.0635 kg/cm³. The lowest value of compression index (Cc) which amounted to 0.125 cm²/min was obtained at 10% sodium lignosulfonate and 10% rice husk ash with 28 days of curing treatment. While the highest coefficient of consolidation (Cv) which amounted to 0.308 cm²/min was obtained by soil with a mixture of 10% sodium lignosulfonate and 10% rice husk ash with 0 days of curing treatment. Sodium lignosulfonate (SLS) and rice husk ash (RHA) can reduce the shrinkage expansion potential of soil based on consolidation testing.